Evaluasi Komunikasi Publik Dalam Dakwah Pembangunan Analisis Retorika Pernyataan Bupati Sumenep Tentang Kemiskinan Petani Di Media Online - Widadi Amado; Abdullah Sattar (Hikmah, 2025)
This study aims to evaluate regional public communication through Aristoteles rhetorical framework by analyzing the statement of the Regent of Sumenep regarding the potential emergence of new poverty among farmers, as reported by Kompas.com. Using a qualitative content analysis method, the research axamines three rhetorical components ethos, pathos, and logos to assess the effectiveness of the regent’s message in the and public responses in online comment sections. The findings indicate that the regent’s rhetoric is imbalanced. His positional ethos as a regional leader is not supported by substantive ethos that reflect moral closeness and empathy toward farmers, resulting in public resistance. The emotional appeal pathos expressed through warnings and expressions of concern triggered negative public emotions due to the absence of concrete solutions. Meanwhile, the logical structure logos appears weak because it relies on partial data and predictive reasoning that lacks comprehensive empirical support. This imbalance contributes to public critism, decreasing trust, and the failure to build and inclucsive development narrative. From the perspective of development focused Islamic communication (dakwah pembangunan), the findings underscore the importance of humanistic, data-driven, and empowerment oriented communication by public officials. Future studies are recommended to conduct comparative rhetorical analyses, integrate media framing examinations, and explore the perspective of farmers as directly affected stakeholders.